Assessing the economic burden of Alzheimer's disease patients first diagnosed by specialists. Issue 1 (December 2016) - Kirson, Noam; Desai, Urvi; Ristovska, Ljubica; Cummings, Alice; Birnbaum, Howard; Ye, Wenyu; Andrews, J.; Ball, Daniel; Kahle-Wrobleski, Kristin
Abstract Background It is not known if there is a differential impact on Alzheimer's disease (AD) diagnosis and outcomes if/when patients are diagnosed with cognitive decline by specialists versus non-specialists. This study examined the cost trajectories of Medicare beneficiaries initially diagnosed by specialists compared to similar patients who received their diagnosis in primary care settings. Methods Patients with ≥2 claims for AD were selected from de-identified administrative claims data for US Medicare beneficiaries (5 % random sample). The earliest observed diagnosis of cognitive decline served as the index date. Patients were required to have continuous Medicare coverage for ≥12 months pre-index (baseline) and ≥12 months following the first AD diagnosis, allowing for up to 3 years from index to AD diagnosis. Time from index date to AD diagnosis was compared between those diagnosed by specialists (i.e., neurologist, psychiatrist, or geriatrician) versus non-specialists using Kaplan-Meier analyses with log-rank tests. Patient demographics, Charlson Comorbidity Index (CCI) during baseline, and annual all-cause medical costs (reimbursed by Medicare) in baseline and follow-up periods were compared across propensity-score matched cohorts. Results Patients first diagnosed with cognitive decline by specialists (n  = 2593) were younger (78.8 versus 80.8 years old), more likely to be male (40 % versus 34 %), and had higher CCI scores and higher medical costs at baseline than those diagnosed by non-specialists (n  = 13, 961). However, patients diagnosed by specialists had a significantly shorter time to AD diagnosis, both before and after matching (mean [after matching]: 3.5 versus 4.6 months, p  < 0.0001). In addition, patients diagnosed by specialists had significantly lower average total all-cause medical costs in the first 12 months after their index date, a finding that persisted after matching ($19, 824 versus $25, 863, p  < 0.0001). Total per-patient annual medical costs were similar for the two groups starting in the second year post-index. Conclusions Before and after matching, patients diagnosed by a specialist had a shorter time to AD diagnosis and incurred lower costs in the year following the initial cognitive decline diagnosis. Differences in costs converged during subsequent years. This suggests that seeking care from specialists may yield more timely diagnosis, appropriate care and reduced costs among those with cognitive decline.